A cell type-specific transcriptomic approach to map B cell and monocyte type I interferon-linked pathogenic signatures in Multiple Sclerosis. (July 2019) - Severa, Martina; Rizzo, Fabiana; Srinivasan, Sundararajan; Di Dario, Marco; Giacomini, Elena; Buscarinu, Maria Chiara; Cruciani, Melania; Etna, Marilena P.; Sandini, Silvia; Mechelli, Rosella; Farina, Antonella; Trivedi, Pankaj; et al.
Abstract: Alteration in endogenous Interferon (IFN) system may profoundly impact immune cell function in autoimmune diseases. Here, we provide evidence that dysregulation in IFN-regulated genes and pathways are involved in B cell- and monocyte-driven pathogenic contribution to Multiple Sclerosis (MS) development and maintenance. In particular, by using an Interferome -based cell type-specific approach, we characterized an increased susceptibility to an IFN-linked caspase-3 dependent apoptotic cell death in both B cells and monocytes of MS patients that may arise from their chronic activation and persistent stimulation by activated T cells. Ongoing caspase-3 activation functionally impacts on MS monocyte properties influencing the STAT-3/IL-16 axis, thus, driving increased expression and massive release of the bio-active IL-16 triggering and perpetuating CD4 + T cell migration. Importantly, our analysis also identified a previously unknown multi-component defect in type I IFN-mediated signaling and response to virus pathways specific of MS B cells, impacting on induction of anti-viral responses and Epstein-barr virus infection control in patients. Taking advantage of cell type-specific transcriptomics and in-depth functional validation, this study revealed pathogenic contribution of endogenous IFN signaling and IFN-regulated cell processes to MS pathogenesis with implications on fate and functions of B cells and monocytes that may hold therapeutic potential. Highlights: Cell type-specific alteration in endogenous Interferon (IFN) system is characterized in Multiple Sclerosis (MS). Altered IFN-regulated genes and pathways are identified in MS B cells and monocytes by an Interferome -based approach. B cells and monocytes from MS patients display an increased susceptibility to caspase-3 dependent apoptotic cell death. Ongoing caspase-3 activation in MS monocytes drives continuous release of bio-active IL-16 amplifying CD4 + T cell migration. Impaired type I IFN-mediated signaling in MS B cells impacts on induction of anti-viral response and EBV infection control.